UTILITY OF LEHANA IN CHILD HEALTH CARE: EVIDENCES FROM AYURVEDA - Pareek Rashmi; Ojha Nisha Kumari; Tiwari Satyendra Kumar (International Journal of Applied Ayurved Research, 2018)
Childhood is a highly consequential period of life that lays an important substratum for the adult years. Because of the underdeveloped immune system, children are more vulnerable for recurrent infections which affect adversely their physical growth and development. Certain drugs prescribed by Ayurveda increase longevity and boost up immune system against various infectious diseases. kāśyapa saṁhitā is the most important contribution of Kāśyapa related to care of the children. Kāśyapa describes Lehana as a procedure to be done in children to increase the digestive power, strength and endurance of the child. It protects and makes the child free from the diseases by improving the immune status. Non-specific immunity in the body is enhanced and average resistance is offered to all infections and the severity of the disease or disease itself is reduced which proves the multi-dimensional approach of Lehana. For this purpose, an attempt has been made to present concept of Lehana as immune enhancing therapy for children.